Removing reactive and acid dyes from single and binary solutions by adsorption on quaternized kenaf core fibers - Al-Tharwani, Intidhar Jabir Idan (2017)
It is estimated that every year 280,000 tonnes of textile dyes are released in textile mill effluent, and unfortunately, all factories are still using water streams for discharging their effluent water. In the wastewater treatment plant, activated carbon is a widely used adsorbent to remove many types of dyes, but it is very expensive. Therefore, adsorption by utilizing different types of agro-residues is one of the alternative materials to remove various types of dyes from solutions.